PENGARUH KEPEMIMPINAN TERHADAP DISIPLIN KERJA PEGAWAI NEGERI SIPIL PADA BADAN KEPEGAWAIAN DAERAH KABUPATEN KUTAI BARAT - Elfreda A Lau, Ewi Darwati H. Eddy Soegiarto K (EKONOMIA, 2015)
The purpose of this research was to determine theeffect of Leadership style and leadership style democratic paternalistis to Work Discipline Civil Service Personnel Agency West Kutai District.Formulation of the problem as posed in this study is : â€œIs there a positive and significant effect between leadership style paternalistis (X1) and the democratic leadership style (X2) on employee discipline (Y), both partially and simultaneouslyâ€. Based on the analysis of the hypothesis that the first and second hypothesis presumed that paternalistic leadership style and leadership democratic equally positive and significant effect on the discipline of employees working at the Office of the Regional Employment Board of West Kutai Regency and the third hypothesis that paternalistic leadership style and leadership style equally democratic influence on the discipline of employees working in the Office of Regional Employment Board received as West Kutai together paternalistic leadership style variables and democratic leadership style has an influence on the discipline of employees working in the Office of the Regional Employment Agency West Kutai. The influence of these variables Analyses of test F, of F is equal to the value of 21,528 with a significance level of 0.000 (95% confidence level) and 3.29 F table then the hypothesis can be accepted because it fits the criteria of F >F. So, when seen from the significant value of 0.000 is less than Î± level of 5%. It can be concluded that the variables paternalistic leadership style and democratic leadership style significantly influence employee discipline employees in the Office of the Regional Employment Agency West Kutai. The contribution of the variables X1, X2 to Y, ie R = 0.757 (75.7%) and R Square of 0.574 (57.4%). This means that there are other factors beyond the study that also affect employee discipline employees in the Office of the Regional Employment Board of West Kutai Regency.T results for each variable are as follows : paternalistic leadership style variable was 3.374 with a significance value of 0.002 is smaller than 0.05, then the hypothesis is accepted, which means t count > t table so evident that paternalistic leadership style significantly influence employee discipline. Democratic leadership style variable was 6.527 with a significance value of 0.000 is smaller than 0.05 and t table 1.690, 6.527 which means that t > t table 1.690, then the hypothesis is accepted because according to criteria t count > t table, so it is evident that the style democratorships significant effect on employee discipline.